Mapping Potential Land Agriculture Paddy Sustainable Use Google Earth Engine in Bekasi Regency - Rahmanda Alif Kurniawan; Supriyadi; Sri Wahyuni (Jurnal Pengetahuan dan Pendidikan, 2025)
This study aims to map and analyze the suitability of sustainable rice paddy land in Bekasi Regency, West Java, an area experiencing rapid urbanization. The research employed a quantitative spatial approach using multi-temporal satellite imagery from the last five years processed through Google Earth Engine (GEE) and ArcGIS 10.3. Land suitability evaluation was conducted by integrating the Analytical Hierarchy Process (AHP) and the Matching Evaluation Approach (MEA) to determine parameter weights and classify land suitability levels. The parameters analyzed included rainfall, temperature, slope, soil type, soil pH, erosion, groundwater recharge, and land use. Land suitability was classified into four categories: very suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N). The results indicate that marginally suitable land (S3) dominates the study area, accounting for 42.21%, followed by moderately suitable land (S2) at 30.44%. Very suitable land (S1) covers only 1.80% of the area, while more than 23% falls into unsuitable categories (N1–N2), mainly in northern coastal areas affected by salinity and drainage constraints. These findings highlight the importance of water availability and soil conditions as dominant factors in rice land suitability. The study provides essential spatial information to support sustainable agricultural planning and land conservation strategies in Bekasi Regency